Identifying the attributes of adherence to tuberculosis treatment in Indonesia: A Delphi study - Prasetyo, Yunus A.; Thanasilp, Sureeporn; Preechawong, Sunida (Narra Sains Indonesia, 2025)
Adherence to tuberculosis (TB) treatment is essential for achieving successful health outcomes. Establishing a consensus among healthcare professionals regarding the definition and key attributes of adherence to TB treatment is essential. The aim of this study was to explore the perspectives of experts and patients on the attributes of adherence to TB treatment. A total of 20 TB specialists and 10 pulmonary TB patients from various regions in Indonesia participated in a three-round Delphi study designed to categorize and validate these attributes. In the first round, participants were interviewed to gather qualitative insights. In the second and third rounds, experts assessed the level of agreement on identified attributes using a five-point Likert scale. The strength of consensus was measured using the interquartile range (IQR), following the best practices outlined in the Conducting and REporting DElphi Studies (CREDES) guidelines. The experts achieved a substantial consensus, with over 85% agreement on the identified attributes. The findings indicated that adherence to TB treatment encompasses the ability of pulmonary TB patients to follow agreed-upon recommendations, including both medication adherence and lifestyle modifications. These lifestyle changes include improved nutritional care, smoking cessation, abstaining from alcohol, stress management, improved physical activity, better sleep, and rest quality, and preventive behaviors related to TB. In conclusion, the findings enhanced the understanding of adherence to TB treatment by highlighting its multifaceted nature. The consensus emphasized that adherence extends beyond medication-taking behaviors to include essential lifestyle changes, underscoring the comprehensive approach needed to support TB patients effectively.